Credit, financial conditions and the business cycle in China - David Lodge; Michel Soudan (European Central Bank (ECB), 2019)
This paper presents empirical evidence of the role of financial conditions in China's business cycle. We estimate a Bayesian-VAR for the Chinese economy, incorporating a financial conditions index for China that captures movements across a range of financial variables, including interest rates and interbank spreads, bond returns, and credit and equity flows. We impose sign restrictions on the impulse response functions to identify shocks to financial conditions and shocks to monetary policy. The model suggests that monetary policy, credit and financial conditions have played an important role in shaping China's business cycle. Using conditional scenarios, we examine the role of credit in shaping economic outcomes in China over the past decade. Those scenarios underscore the important role of credit growth in supporting activity during the past decade, particularly the surge in credit following the global financial crisis in 2008. The financial tightening since the end of 2016 has contributed to a modest slowing of credit growth and activity.
Keywords: E32; E44; E51; E17; 330; Monetary policy; credit conditions; financial conditions index; Bayesian VAR